Penerapan Navmesh Dengan Algoritma A Star Pathfinding Pada Game Edukasi 3d Go Green - Linda Safira; Paulus Harsadi; Sri Harjanto (STMIK Sinar Nusantara, 2021)
Cleanliness is one of the requirements to create a healthy living environment. But in reality, not everyone have a concern for environmental hygiene and health. For this reason, learning about the importance of caring for environmental cleanliness must be instilled early on. One interesting method to provide learning about environmental cleanliness can be through games. With the 3D visualization of this environmental cleanliness game, it is an effort to raise awareness of the importance of environmental hygiene and health in the community. The location used in making this game is Campus 1 Poltekkes Surakarta. The purpose of this study is implementation of Navmesh with the A Star (A*) Pathfinding Algorithm on the characters so that players can find the trash location point and the location point of the tree with the shortest route. Making this game uses the GDLC (Game Development Life Cycle) method with stages of Initiation, Pre Production, Production, Testing, Beta and Release. This game can be played on desktop and mobile devices. The results of the research that has been done are seen from the algorithm simulation testing is the nodes that are passed by as many as 50 nodes, where there are duplicate data as many as 7 nodes due to real time systems that read nodes over and over. Thus, the application accuracy rate reaches 86%.